Empirical model of natural frequency for single span integral bridge - Ibrahim, Muhammad Khairil (2020)
Natural frequency has been used as a reliable indicator for damage and condition assessment in civil engineering application, where the in situ natural frequency is compared to the theoretical natural frequency to determine the condition of a structure. However, the theoretical natural frequency for integral abutment bridge can be difficult to attain. It involves modelling for full bridge and required extended knowledge of bridge modelling. Furthermore, the integral abutment bridges in Malaysia are unique by themselves, due to the use of different standard T-Beam by JKR and bored piles as the supporting element which are different from other countries. Although there are several studies on the model equation on predicting the natural frequency of a bridge, the prediction model for integral type bridge is yet to be discovered. Therefore, this research is carried out to produce model equation to determine theoretical natural frequency for integral abutment bridge. This research consist of two major tasks. The first task is to produce the theoretical model. The total numbers of 168 finite element models of integral abutment bridge were modelled using ABAQUS software with considering a combination of various bridge configurations, including length, number of beam, modulus of elasticity and soil types. Each combination model of integral abutment bridge was analysed using Lanzcos Eigen Extraction to obtain the natural frequency. The natural frequency was then recorded for further analysis. A step-wise multiple linear regression approach was adopted to develop the prediction model describing natural frequency relationship for a various combination of bridge configuration. Then, the model equation was validated using empirical data from experimental modal analysis as the second task of the research. The data were collected on site from three different integral abutment bridges using impulse hammer as excitation method. Dewesoft signal processing software was used to acquire the raw data from the test. Then, the data was further analysed using ME scope software. The determination of the natural frequency from this software was based on the coherent, real part and modal indicator function. Subsequently, the theoretical and observed natural frequencies were compared statistically using T-test. The prediction model equation of natural frequency shows a good conformance with the experimental modal analysis obtained at site. The model equation describing the natural frequency for integral abutment bridge is found to be influenced by length, number of beam and modulus of elasticity significantly.